Impact of Pharmacist Integration Into Primary Care on Reimbursement for Hospital Follow-Up Visits - Mackenzi Meier; Grace Simpson; Megha Patel; Chelsea A. Keedy (SAGE Publishing, 2023)
Background: The financial and clinical impact of transitional care management (TCM) outcomes through pharmacist integration within primary care is not well described. Objectives: The primary objective of this study was to determine the financial impact of pharmacist conducted post-discharge phone calls. The secondary objectives included readmission rates and number of interventions. Methods: A computer-generated list identified patients discharged from St. Joseph's/Candler Health System (SJ/C) with a listed primary care provider within the SJ/C Primary Care Medical Group at Eisenhower from November 1, 2019 to April 30, 2020. Eligible patients who received a post-discharge phone call from a pharmacist were compared to those who received a call by another staff member. Data was collected regarding the financial impact of pharmacist conducted post-discharge phone calls. Readmission rates and medication related interventions were also assessed. Results: There were 104 patients discharged meeting criteria. Twenty-four patients were contacted by a pharmacist resulting in 20 subsequent hospital follow up appointments scheduled with the provider. Total amount billed for those appointments was $4220 (average of $211 per visit). Twenty-five calls were made by non-pharmacist staff with 23 appointments scheduled. Total amount billed for those appointments was $2445 (average of $106 per visit). Increased reimbursement was generated by a qualifying 2-way communication by the pharmacist as outlined by Center for Medicaid and Medicare Services enabling providers to bill for a TCM visit versus standard office visit. Pharmacists made 33 clinical interventions including medication reconciliation, medication procurement, referrals, lab orders, and education. One intervention was made by non-pharmacist staff. The 30-day readmission rate for pharmacist contacted patients was 8% versus 12% for non-pharmacist contacted patients. Conclusions: Pharmacist involvement in TCM while integrated into a primary care office is previously not well described. This data highlights an opportunity for pharmacists to demonstrate sustainability and improved outcomes related to TCM.